The interaction between warming and enrichment accelerates food‐web simplification in freshwater systems - Bonnaffé, W; Danet, A; Leclerc, C; Frossard, V; Edeline, E; Sentis, A (Wiley, 2024)
Nutrient enrichment and climate warming threaten freshwater systems. Metabolic theory and the paradox of enrichment predict that both stressors independently can lead to simpler food‐webs having fewer nodes, shorter food‐chains and lower connectance, but cancel each other's effects when simultaneously present. Yet, these theoretical predictions remain untested in complex natural systems. We inferred the food‐web structure of 256 lakes and 373 streams from standardized fish community samplings in France. Contrary to theoretical predictions, we found that warming shortens fish food‐chain length and that this effect was magnified in enriched streams and lakes. Additionally, lakes experiencing enrichment exhibit lower connectance in their fish food‐webs. Our study suggests that warming and enrichment interact to magnify food‐web simplification in nature, raising further concerns about the fate of freshwater systems as climate change effects will dramatically increase in the coming decades.